2019
DOI: 10.1021/acsanm.9b00485
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer and Near-Field Mechanisms in Plasmonic Gold-Nanoparticle-Modified TiO2 Photocatalytic Systems

Abstract: The major mechanism responsible for plasmonic enhancement of titanium dioxide photocatalysis using gold nanoparticles is still under contention. This work introduces an experimental strategy to disentangle the significance of the charge transfer and near-field mechanisms in plasmonic photocatalysis. By controlling the thickness and conductive nature of a nanoparticle shell that acts as a spacer layer separating the plasmonic metal core from the TiO2 surface, field enhancement or charge transfer effects can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 37 publications
1
46
1
Order By: Relevance
“…The synthesis and characterization of metal nanoparticles has gained a lot of attention during the last decade due to their unique electronic, thermal, optical, and catalytic properties leading to important technological applications such as plasmonic photo‐ and electrocatalysis, surface‐enhanced Raman‐spectroscopy, (bio)‐sensors, and nanoelectronic devices . Bimetallic nanoparticles are of specific interest because of their versatility and tunability mainly for (photo)catalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and characterization of metal nanoparticles has gained a lot of attention during the last decade due to their unique electronic, thermal, optical, and catalytic properties leading to important technological applications such as plasmonic photo‐ and electrocatalysis, surface‐enhanced Raman‐spectroscopy, (bio)‐sensors, and nanoelectronic devices . Bimetallic nanoparticles are of specific interest because of their versatility and tunability mainly for (photo)catalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic photocatalysts can be categorized into the hot-electron transfer (HET)-type 23,24 and the local electric eld-enhanced (LEFE)-type [25][26][27][28] or the plasmon-resonant energy-transfer-type. 29 Here the basic action mechanisms of the HET-and LEFE-type plasmonic photocatalysts are explained for the typical heteronanostructures of Au NP-loaded semiconductors (Au/semiconductor) and Au NP-incorporated semiconductors (Au@semiconductor) including Au NP (core)-semiconductor (shell) nanohybrids, respectively.…”
Section: Action Mechanisms Of Plasmonic Photocatalystsmentioning
confidence: 99%
“…The additional advantage of fully embedding the nanoparticles into the photocatalytic TiO2 film can be rationalized as follows: (i) under UV light irradiation electron-hole pairs are generated in the TiO2 semiconductor, while the metal nanoparticles solely act as passive electron sinks, resulting in less recombination events. [20] (ii) On the other hand, previous research has also shown that for Au/TiO2 composites under visible light illumination, direct "hot electron" injection from the excited plasmonic nanoparticles into the conduction band of TiO2 plays an important role, [21,22] as well as an increase of the electromagnetic near-field within a 3 nm radius surrounding the plasmonic nanoparticle, as investigated by Asapu et al [23,24] Regardless of the excitation wavelength, maximising the direct contact interface between the nanoparticle and the semiconductor is of paramount importance for both of these electron and energy transfer processes. As a consequence, by partially or fully embedding the nanoparticles in the TiO2 matrix, the contact interface is increased substantially and may lead to considerably higher photocatalytic activities (Figure 1).…”
Section: Introductionmentioning
confidence: 98%